Who was Jesus? - Wright, N. T. (Nicholas Thomas) (Grand Rapids, Michigan : William B. Eerdmans Publishing Co., 2014)
Originally published in 1993 and reprinted numerous times, N. T. Wright's Who was Jesus? considers many questions raised by three controversial books about Jesus: Barbara Thiering's Jesus the man, A. N. Wilson's Jesus: a life, and John Shelby Spong's Born of a Woman. While Wright agrees with those authors that the real, historical Jesus has many surprises in store for institutional Christianity, he also presents solid reasons for discounting their arguments, claiming that they "fail to reach anything like the answer" as to who Jesus really was. Written from the standpoint of professional biblical scholarship yet assuming no prior knowledge of the subject, Who was Jesus? shows convincingly that much can be gained from a rigorous historical assessment of what the Gospels say about Jesus. This is a book to engage skeptics and believers alike.
1. The Portraits and the puzzles -- 2. Barbara Thiering: Jesus in code -- 3. A. N. Wilson: a moderately pale Galilean -- 4. John Spong: the bishop and the birth -- 5. Jesus revisited.
Includes bibliographical references.
pdf version (accessed September 21, 2018).
Master record variable field(s) change: 050, 600
Keywords: Jesus Christ -- Historicity; Thiering, B. E; Wilson, A. N., -- 1950-; Spong, John Shelby; Bible. -- Criticism, interpretation, etc; Jesus Christ; Bible; RELIGION / Christian Theology / Christology; Historicity of Jesus Christ; Electronic books; Criticism, interpretation, etc